Altered visual information processing systems in bipolar disorder: evidence from visual MMN and P3 - Maekawa, Toshihiko; Katsuki, Satomi; Kishimoto, Junji; Onitsuka, Toshiaki; Ogata, Katsuya; Yamasaki, Takao; Ueno, Takefumi; Tobimatsu, Shozo; Kanba, Shigenobu (Frontiers in Human Neuroscience, 2013)
Objective: Mismatch negativity (MMN) and P3 are unique ERP components that provide objective indices of human cognitive functions such as short-term memory and prediction. Bipolar disorder (BD) is an endogenous psychiatric disorder characterized by extreme shifts in mood, energy, and ability to function socially. BD patients usually show cognitive dysfunction, and the goal of this study was to access their altered visual information processing via visual MMN (vMMN) and P3 using windmill pattern stimuli. Methods: Twenty patients with BD and 20 healthy controls matched for age, gender, and handedness participated in this study. Subjects were seated in front of a monitor and listened to a story via earphones. Two types of windmill patterns (standard and deviant) and white circle (target) stimuli were randomly presented on the monitor. All stimuli were presented in random order at 200-ms durations with an 800-ms inter-stimulus interval. Stimuli were presented at 80% (standard), 10% (deviant), and 10% (target) probabilities. The participants were instructed to attend to the story and press a button as soon as possible when the target stimuli were presented. Event-related potentials were recorded throughout the experiment using 128-channel EEG equipment. vMMN was obtained by subtracting standard from deviant stimuli responses, and P3 was evoked from the target stimulus. Results: Mean reaction times for target stimuli in the BD group were significantly higher than those in the control group. Additionally, mean vMMN-amplitudes and peak P3-amplitudes were significantly lower in the BD group than in controls. Conclusions: Abnormal vMMN and P3 in patients indicate a deficit of visual information processing in bipolar disorder, which is consistent with their increased reaction time to visual target stimuli. Significance: Both bottom-up and top-down visual information processing are likely altered in BD.